Analisis Penggunaan Online Integrated Banking Sharia System (OLIBSS) dalam Meningkatkan Akurasi dan Efisiensi Proses Transaksi Tabungan Wadiah di BPRS HIK Parahyangan - Amalia Marliani; Dudang Gojali (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the use of Online Integrated Banking Sharia System (OLIBSS) in improving the accuracy and efficiency of wadiah savings transaction processes at BPRS HIK Parahyangan. This study uses a qualitative approach with primary data collection methods through interviews and secondary data obtained from relevant internal documents. The results of the study indicate that the implementation of OLIBSS makes a significant contribution to improving the accuracy of recording wadiah savings transactions, minimizing human error, and accelerating operational processes that were previously carried out manually. In addition, this system also supports efficiency in reporting and internal supervision. Thus, the use of OLIBSS has proven effective in supporting a reliable accounting information system that is in accordance with sharia principles.